Energy absorption of kirigami modified corrugated structure - Li, Z.; Chen, Wensu; Hao, Hong; Yang, Q.; Fang, R. (ELSEVIER SCI LTD, 2020)
In this study, a new Kirigami corrugated structure is designed. Dash lined cuts across each row of corrugated structures are introduced and then folded inwards. The proposed Kirigami (cut and fold) modification provides extra vertical crushing resistance and constraints between the structure faces. Out-of-plane quasi-static tests are carried out for both conventional corrugated structures and Kirigami corrugated structures made of aluminium thin sheets. The numerical models with imposed imperfections are calibrated with the test data and then used for the dynamic crushing analysis of the structures under various loading rates. Key parameters such as initial peak force, average crushing resistance and energy absorption are compared among the conventional and Kirigami corrugated structures. Significant changes in deformation modes and great enhancement of energy absorption capacity under out-of-plane crushing are shown for the proposed Kirigami corrugated structures as compared to conventional corrugate structures. Furthermore, crushing resistance of the proposed Kirigami corrugated structure is less sensitive to imperfections. Great potential of the proposed Kirigami modification technique on corrugated structures is demonstrated with minimal change in its original manufacturing process but substantial enhancement in energy absorption capacities.